Gender Comparison of Emotional Intelligence of University Students (Journal of Education and Educational Development, 2020)
Emotional intelligence is a contributing construct to learning and other personal and career developments. It is a perplex notion involving many conceptions which resulted in various tools of emotional intelligence. University education is a terminal stage when young people are ready to enter the job arena and are expected to be emotionally sound. Numerous studies have been carried out on the differentiation of emotional intelligence of the learners, particularly at graduate and post-graduate levels. This study is an attempt to investigate emotional intelligence of the university students. Since there are differences in the findings of various studies in terms of gender; therefore, this study also considers to explore the discrepancy of the emotional cognizance of the male and female learners at university level. The target participants of this investigation were the students of all five faculties of a university in Khyber Pukhtunkhwa, a province in Pakistan. The Wong and Law Emotional Intelligence Scale (WLEIS) developed by Wong and Law (2002) was used for data collection. The outcomes of the investigation showed that female learners were ahead of male in emotional intelligence. Further, the learners of business and economics had superior level of emotional intelligence, while students of Arts and Humanities had inferior level of emotional intelligence. The study put forward some valuable suggestions, particularly through curricula enhancement and for further research activities.